Modeling and molecular dynamics indicate that snake venom phospholipase B-like enzymes are Ntn-hydrolases - Coronado, Mônika Aparecida [UNESP]; da Silva Olivier, Danilo [UNESP]; Eberle, Raphael Josef [UNESP]; do Amaral, Marcos Serrou; Arni, Raghuvir Krishnaswamy [UNESP] (Elsevier, 2018)
Phospholipase-B-like (SVPLB-like) enzymes are present in relatively small amounts in a number of venoms, however, their biological function and mechanisms of action are un-clear. A three-dimensional model of the SVPLB-like enzyme from Crotalus adamanteus was generated by homology modeling based on the crystal structures of bovine Ntn-hydrolyases and the modeled protein possesses conserved domains characteristic of Ntn-hydrolases. Molecular dynamics simulations indicate that activation by autocatalytic cleavage results in the removal of 25 amino acids which increases accessibility to the active site. SVPLB-like enzymes possess a highly reactive cysteine and are hence amidases that to belong to the N-terminal nucleophile (Ntn) hydrolase family. The Ntn-hydrolases (N-terminal nucleophile) form a superfamily of diverse enzymes that are activated autocatalytically; wherein the N-terminal catalytic nucleophile is implicated in the cleavage of the amide bond.
Keywords: Crotalus adamanteus; Molecular dynamics; Molecular modeling; Ntn-hydrolase; Snake venom phospholipase B